Animal As Machine The Quest to Understand How Animals Work and Adapt. - Anctil, Michel (McGill-Queen's University Press, 2022)
Animal as Machine explores the life, work, and ideas of scientists who subscribed to mechanistic concepts to explain how animals process food, breathe, circulate their blood, and sense their environment. A remarkable story of the larger-than-life personalities and historical episodes that marked the emergence of animal physiology.